Legal Protection for Whistleblowers from an Indonesian Employment Perspective - Giovanny Syalshabila; Padrisan Jamba (Jurnal Multidisiplin Sahombu, 2026)
Whistleblowing plays a strategic role in maintaining transparency and accountability within institutions, including in the context of employment relations. However, whistleblowers often face retaliation in the form of dismissal, psychological pressure, or unfair transfers. In Indonesia, regulations explicitly protecting whistleblowers from retaliation are still absent. The absence of an anti-retaliation clause in Law Number 13 of 2003 concerning Manpower indicates a weak legal framework for whistleblowers in the workplace. This study aims to analyze the legal gaps related to the protection of whistleblowers, identify socio-cultural factors that exacerbate the risk of retaliation, and compare protection models in other countries such as Malaysia and Australia. The methods used are a normative juridical approach and comparative law. The results show that Indonesian regulations are still partial and do not provide strict sanctions for perpetrators of retaliation. Therefore, legal reform is needed, including anti-retaliation provisions in the Employment Law and collaborating with the Witness and Victim Protection Agency (LPSK). This reform is crucial for strengthening good governance practices in the workplace and ensuring legal protection for workers with integrity.